ACCURATE QUANTIFICATION OF PURE OR IMPURE SUBSTANCES IN THE MICRO- TO MILLIGRAM RANGE BY 1H-NMR - Schripsema, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Frequently the accurate quantification of micro- to milligram quantities is needed, e.g. for the preparation of standard solutions for GC or HPLC quantification, or for biological assays. Weighing these quantities is imprecise and dilutions should be prepared, which is often not possible due to unavailability of larger quantities. Another factor to be considered is that the reference compounds are often impure. Therefore, the weighing of reference standards can lead to large systematic errors in the assays. 1H-NMR is, in principle, very suitable for the accurate quantification of specific compounds. In the present study, small quantities of cyanobacterial toxins, to be used as standards for GC and HPLC analysis, were quantified, and also a series of novel iridoid glucosides, isolated from Pentas lanceolata, was quantified prior to the determination of the specific rotation of the compounds. Two cyanobacterial toxins: Anatoxin-a and [D-Leu1]-Microcystin LR have been quantified using 1H-NMR. To obtain an accurate quantification to both samples an accurate quantity of pyridine was added as internal standard. Relative to the signals of pyridine, it was possible to determine the precise quantity of the toxins, using specific signals, which did not have any overlap with other signals. In the case of anatoxin-a It was possible to obtain an accurate quantification of a 22.4 microgram quantity using a standard 400 MHz spectrometer. In the case of the iridoid glucosides the major advantage was the insensitivity to impurities in the samples Acknowledgements: FAPERJ, CNPq.